Evaluation of high yielding strains of Oyster mushroom (Pleurotus spp.) - Shroff, Sharad (Mushroom Research, 2016)
Five strains of oyster mushroom were tested for various parameters such as time taken for spawn run and pin head initiation, days taken for first harvest, fruit body/bag average weight of fruit body, yield and biological efficiency. Results indicate that highest biological efficiency was recorded in strain R-13-13-05 (96.6 %) followed by strain R-13-13-07 (75.3 %), R-13-13-03 (74.8 %) and R-51 (66.4 %), respectively, and Lowest BE was observed in strain R-13-13-04 (58.4 %). Days required for spawn run was minimum for strain R-13-13-05 (17 days) followed by R-13-13-04 (17.67 days), Whereas strain R-13-13-3 took maximum time of 20.33 days for completion of spawn run Pin head initiation was first reported in strain R-13-13-5 (20.67 days) followed by strain R-51 (23.50 days), R-13-13-04 (24.17 days) and R-13-13-03 (24.67 days), respectively. Maximum days, required for pin head initiation, were in strain R-13-13-07 (25.0 days). First harvesting was done in strain R-13-13-05 (after 25.33 days of spawning) followed by strains R-13-13-03, R-13-13-07, R-51 and R-13-13-04 (after 27.33, 27.33, 27.50, 29.50 days of spawning, respectively). Among all the strains, tested in the experiment, strain R-13-13-07 recorded highest fruit body weight (26.55 g) followed by R-13-13-04 (25.50 g), strains R-1313-05, (19.86g ) and R-51 (17.33 g ), respectively. Lowest weight, per fruit body, was recorded in strain R-13-13-03 (14.52 g). Strain R-13-13-03 yielded maximum number of fruit bodies per bag (61.33) followed by R-51 (60.33 f),. Whereas, minimum number of fruit bodies observed in strain R-13-13-07 (31.0).Â